The Internet Research Agency Campaign to Influence the 2016 US Presidential Elections: A Rhetorical Analysis - Nelson N; Hodgetts D; Chamberlain K (John Wiley and Sons Ltd, 2025)
The centrality of information and communicative processes in persuading society has, historically, made the media one of the key networks of power and influence in society. The rapid expansion of social media platforms has, however, enabled revolutionary changes in how this power is wielded and how persuasion occurs. This has had a profound impact on how political, economic, and social issues are understood and addressed. While a comprehensive body of social psychological theory and applied practice on the topic of persuasion has been developed over many years, persuasion in the contemporary social media environment is one that researchers are yet to fully understand. Methods for achieving this understanding continue to evolve. This article draws on a large corpus of material (2218 Facebook advertisements and metadata) which documented the Russian Internet Research Agency campaign to influence the outcome of the 2016 US presidential elections. Drawing on Aristotle's rhetorical framework, this article presents a process analysis to understand how political persuasion is undertaken in the contemporary social media environment. The findings provide new insights into the social psychological processes of persuasion in contemporary society and demonstrate the utility of a rhetorical framework in understanding persuasion campaigns in dynamic digital settings.
Keywords: 2016 US presidential elections; Aristotle; persuasion; rhetorical analysis; social influence; social media; social psychology